Taxonomic revision of the oil-collecting bee subgenus Epicharis (Epicharitides) Moure, 1945 (Hymenoptera: Apidae), with the description of two new species - Villamizar, Germán; Vivallo, Felipe (European Journal of Taxonomy, 2024)
A taxonomic revision of the oil-collecting bees of the subgenus Epicharis (Epicharitides) Moure, 1945 is provided. A total of nine species were recognized: E. cockerelli Friese, 1900; E. duckei Friese, 1901; E. iheringi Friese, 1899; E. luteocincta Moure & Seabra, 1959; E. minima (Friese, 1904); E. obscura Friese, 1899, and E. rufescens Moure & Seabra, 1959, along with E. mesoamericana sp. nov. and E. lia sp. nov., two new species from the Central American and Amazonian provinces, respectively. Redescriptions, diagnoses, and figures of specimens of both sexes, floral records, distribution maps, an identification key, and an updated catalogue of all species of the group are also provided. In addition, the lectotype of E. duckei was also designated to stabilize the application of the name.